Perbandingan Kuat Tekan Dan Kuat Lentur Beton Mutu Tinggi Dengan Menggunakan Berbagai Merk Semen Di Kota Pekanbaru: Comparison of the Strength and Strength of Bending of High Quality Concrete by Using Various Brands Cement in Pekanbaru City - Roza Mildawati (UIR Press, 2018)
[ID] Concrete is a very popular building material used in the world of construction services, consisting of a mixture of Portland Cement (PC) or other hydraulic cement, fine aggregates, coarse aggregates and water, with or without using additional materials. The quality of materials such as cement also greatly affects the strength of the concrete after hardening, so the selection of cement quality must be in accordance with the concrete planning regulations in order to obtain optimal results. In Indonesia there are many new cement factories that produce to meet the needs of the community, one of which is the Conch brand cement. So in connection with the above, Conch cement can be examined to compare the value of compressive strength and flexural strength with old cement, namely cement Padang, Tiga Roda, Holcim and Bosowa which are generally always used in concrete planning at this time.The purpose of this study was to determine the comparison of compressive strength and flexural strength of the concrete and the multiplier between cement Padang, Three Wheels and Conch at 28 days of age. In this study using the method SNI 03-2834-2000. With cylindrical test specimens (150 mm x 300 mm) and size beams (150 mm x 150 mm x 600 mm) three specimens were made for each cement.The maximum concrete compressive strength is found in Padang cement with a compressive strength of 45.86 Mpa, for the minimum compressive strength found in Tiga Roda cement with compressive strength value of 40.19 Mpa and for the compressive strength of cement Conch there is a second with compressive strength value 42.84 Mpa. From the explanation above, the results of 28 days of concrete compressive strength with each cement brand still not reached the planned concrete compressive strength of 38 MPa. The maximum concrete flexural strength is found in Padang cement with a flexural strength value of 5.03 Mpa, for a minimum flexural strength value found in Tiga Roda cement with a flexural strength value of 3.96 Mpa and for the value of Conch cement compressive strength there is a second with flexural strength 4.43 Mpa. From the explanation above, the results of 28 days of concrete flexural strength with each cement brand that has not reached the 4.4 Mpa plan, namely the three-wheeled cement brand. [EN] Concrete is a very popular building material used in the world of construction services, consisting of a mixture of Portland Cement (PC) or other hydraulic cement, fine aggregates, coarse aggregates and water, with or without using additional materials. The quality of materials such as cement also greatly affects the strength of the concrete after hardening, so the selection of cement quality must be in accordance with the concrete planning regulations in order to obtain optimal results. In Indonesia there are many new cement factories that produce to meet the needs of the community, one of which is the Conch brand cement. So in connection with the above, Conch cement can be examined to compare the value of compressive strength and flexural strength with old cement, namely cement Padang, Tiga Roda, Holcim and Bosowa which are generally always used in concrete planning at this time.The purpose of this study was to determine the comparison of compressive strength and flexural strength of the concrete and the multiplier between cement Padang, Three Wheels and Conch at 28 days of age. In this study using the method SNI 03-2834-2000. With cylindrical test specimens (150 mm x 300 mm) and size beams (150 mm x 150 mm x 600 mm) three specimens were made for each cement.The maximum concrete compressive strength is found in Padang cement with a compressive strength of 45.86 Mpa, for the minimum compressive strength found in Tiga Roda cement with compressive strength value of 40.19 Mpa and for the compressive strength of cement Conch there is a second with compressive strength value 42.84 Mpa. From the explanation above, the results of 28 days of concrete compressive strength with each cement brand still not reached the planned concrete compressive strength of 38 MPa. The maximum concrete flexural strength is found in Padang cement with a flexural strength value of 5.03 Mpa, for a minimum flexural strength value found in Tiga Roda cement with a flexural strength value of 3.96 Mpa and for the value of Conch cement compressive strength there is a second with flexural strength 4.43 Mpa. From the explanation above, the results of 28 days of concrete flexural strength with each cement brand that has not reached the 4.4 Mpa plan, namely the three-wheeled cement brand.